Positive management of the university - Krzysztof Leja (Gdańsk University of Technology, Faculty of Management and Economics, 2015)
The prevailing view held at contemporary Polish universities is that their main goal is to achieve effects measured by indicators, which applies to each element of their mission: education, research and the third mission, whereas the means to accomplish this goal consists of increasing the requirements and motivating by the “carrot and stick” approach. That approach discounts the importance of building a positive relationship between members of the staff and undertaking activities intended to create a situation where hedonistic joy of work will dominate in universities. This in turn will promote integration of the academic environment and induce employees to strive for mastery to find pleasure and satisfaction rather than to achieve specific effects of their activity, which eventually will lead to better efficiency. The main goal of the paper is to demonstrate that contemporary universities may be improved by synthesis of strategic antinomies, i.e. seeking the possibility of combining opposite approaches to solving problems concerning university organization and management. The motivation method used at universities to date turns out to be ineffective; therefore, following the positive thinking idea formulated by Martin Seligman, the author of the study proposes to apply synthesis of strategic antinomies (paradoxes) observed in universities and use the results to counteract the noticeable trauma of academic communities and replace it with positive thinking, consisting of the aspiration to discover and understand phenomena, the sense of belonging to the academic environment and building positive relationships with that environment. Such an approach is in agreement with the “philosophy” proposing to replace the dictatorial “tyranny of the OR” (either 'a' or 'b'”, but not both at the same time with the genius of the AND (both 'a' and 'b'), applied by visionary organizations, such as universities should strive to become.
Keywords: I23; 330; strategic paradoxes; university organization and management; resistance to changes; positive management